Detection of DNA of Rickettsia and Orientia tsutsugamushi in rodents and ectoparasites in Ha Giang province - Lan Anh, Le Thi; Viet Cuong, Vo; Van Toan, Trinh; Thi Hong Nhung, Ho; Van Anh, Le Thi; Thi Thu Thuy, Can; Thi Ha Giang, Pham; Thi Thanh Nga, Bui; Thi Lan Anh, Bui; Van Chau, Nguyen (Vietnam Journal of Biotechnology, 2020)
Rickettsial fever is one of a zoonotic disease which is caused by bacteria genus Rickettsia. The ectoparasites such as ticks, mites, fleas, lice... were demonstrated as the main transmited vectors through host reservoirs are rodents and small animals including mice, squirrels, mink... In this study, the rodents and ectoparasites species were identified. The molecular detection of Rickettsia was also performed. In 2018, 83 rats were trapped in 2 villages Thanh Duc and Phu Linh, Vi Xuyen district, Ha Giang province, in which 48.2% mice were found as house mice Rattus flavipectus, 21.7% was forest mice R. rattus, 12% was R. fulvescens, 8.4% was R. nitidus, the remaining rates were R. bowersi, Mus. pahari, Leopoldamys sabanus, Mus musculus and R. niviventer, accounting for 1.2% - 3.6%. The ectoparasites survey found 5 chigger mite species including Leptotrombidium (Leptotrombidium) deliense, Ascoschoengastia (Laurentella) indica, Garhliepia (Walchia) rustica, Lorilutum oreophilum and Shunsenia sp as well as 3 gamasid mite species such as Laelaps (Echidninus) sedlaceki, Laelaps (Laelaps) nuttali and Lenstivalius klossi bispiniformis. The result indicated that 19.3% and 10.8% mice were positive with Ricketsia spotted fever group (SFG) and Rickettsia typhi, respectively by real-time PCR. The nested PCR result showed that 19.4% R. flavipectus mice and 10% L. (L.) deliense chigger mites were positive with Orientia tsutsugamushi.